Influence of saliva on the oral microbiota. Issue 1 (February 2016) - Marsh, Philip D.; Do, Thuy; Beighton, David; Devine, Deirdre A.
Abstract: Saliva plays a major role in determining the composition and activity of the oral microbiota, via a variety of mechanisms. Molecules, mainly from saliva, form a conditioning film on oral surfaces, thus providing receptors for bacterial attachment. The attached cells use saliva components, such as glycoproteins, as their main source of nutrients for growth. Oral bacteria work sequentially and in a concerted manner to catabolize these structurally complex molecules. Saliva also buffers the pH in the biofilm to around neutrality, creating an environment which is conducive to the growth of many oral bacteria that provide important benefits to the host. Components of the adaptive and innate host defences are delivered by saliva, and these often function synergistically, and at sublethal concentrations, so a complex relationship develops between the host and the resident microbiota. Dysbiosis can occur rapidly if the flow of saliva is perturbed.